CROSS-CULTURAL PRAGMATICS OF INDONESIAN SPEECH ACTS BY FILIPINO YOUTUBE CONTENT CREATOR - Abdul Ghafur; Yunisrina Qismullah Yusuf; Mohd. Harun; Ramli Ramli; Denni Iskandar (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
In Indonesian digital space, recently, there has been a noticeable increase in Filipino gaming content creators speaking in Indonesian. This phenomenon is interesting because it shows that the digital platforms have become key spaces for intercultural communication, identity expression, and language interaction in modern society. However, research on Indonesian speech acts used by foreign speakers, particularly Filipino content creators, is still very limited. Therefore, this study aims to examine how Filipino content creators perform Indonesian speech acts in digital communication. Several Indonesians and Filipinos creators, who is communicating in the digital space, were selected as the data source due to their high audience engagement and consistent use of Indonesian in digital communication. Such communication practice makes them appropriate representatives of cross-cultural language practices in online environments. Through a qualitative analysis, the specific eight hours of video data were transcribed and categorized according to Austin and Searle’s speech act framework (locutionary, illocutionary, and perlocutionary). Such categorization is displayed into tables to identify patterns of use. This systematic analytical procedure enhances interpretive reliability and reveals recurring pragmatic patterns within naturally occurring discourse. The study identified a total of 97 speech acts produced by Filipino content creators. The analysis shows that Filipino content creators tend to use illocutionary speech acts with harsher language and a sarcastic style. Furthermore, content creators also use locutionary acts that employ descriptive sentences and informal or casual language. Meanwhile, in perlocutionary acts, content creators generally receive positive responses from their audience, which is most likely influenced by the entertaining and light-hearted nature of their videos. These findings indicate that Filipino content creators, despite being non-native Indonesian speakers, demonstrate strong pragmatic awareness by strategically performing social actions, managing interpersonal relations, and sustaining audience engagement. Their speech reflects how digital contexts facilitate pragmatic experimentation, enabling second-language users to adapt linguistic resources to interactional goals such as persuasion, rapport-building, and identity construction. This study contributes to the development of cross-cultural pragmatic studies and can serve as a reference for teaching Indonesian as a foreign language in the digital era by emphasizing the pedagogical value of authentic digital discourse in fostering learners’ pragmatic competence and intercultural communicative skills in real-world communication.